Pelatihan Komunikasi Pelayanan Untuk Peningkatan Kepuasan Pelanggan Di Masa Pandemi - Prasojo, Prasojo; Arifianto, M Lukman; Irfansyah, Azhar (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
The covid-19 pandemic has entered human life in a short time. This causes several aspects of human life to experience shocks, including currency. Many product scopes have been affected by this pandemic, including the food and beverage business sector. The food and beverage business sector must remain active and think of ways to attract customers and make these customers satisfied with the services provided. In the context of customer satisfaction, customer satisfaction is not necessarily obtained at that time instantly because their needs are met. Customer satisfaction is established and maintained by fulfilling personal needs and touching the emotional aspects of customers. Solidarity, the sensitivity of being part of a family, is the satisfaction customers want during the pandemic and becomes the new normal.